Estoque de carbono e estabilidade de agregados de um latossolo vermelho distrófico, sob diferentes manejos - Rozane, Danilo Eduardo [UNESP] (2010)
These systems of soil use and management are very important in carbon supply and stability of aggregates, because affect directly culture yields. The aim of this project is to evaluate the carbon supply and stability of Haplustox aggregates under different managements. It was utilized a completely randomized experimental design in split plot scheme, with six replications. Thus, the treatments utilized were three different soil managements (native forest, pasture with Tanzania grass and corn). The plots were consisted by three layers (0-10; 10-20 and 20-30 cm) and were analyzed to determined the organic matter, organic carbon supply of soil (layers and equivalent soil mass methods) and weighed average diameter (DMP) and geometrical average diameter (DMG). The results indicated that the evaluated managements systems affected the size of soil aggregates of the ground and in its distribution in the layer of 0 - 30 cm of depth. The greatest accumulation of carbon were in the surface layers, although, there were not variation between the management systems.